Pengaruh Lingkungan Kerja dan Motivasi Kerja terhadap Kepuasan Kerja Karyawan - Anggun Cahya Ningrum; Munawaroh Munawaroh (Jurnal Manajemen Riset Inovasi, 2025)
This study aims to determine and analyze the influence of work environment and work motivation on employee job satisfaction, both partially and simultaneously. The population of this study were employees of PT. Indah Kiat, Serang Regency, Banten with a research sample of 100 people. This study uses primary data sources by distributing questionnaires in the form of a Likert scale. The data analysis technique used is multiple linear regression with the help of the SPSS version 25 program. The results of the study indicate that there is a positive and significant influence between the work environment and work motivation on job satisfaction, both partially and simultaneously.